The Role of Leadership Style, Organizational Culture, and Career Development in Improving Human Resource Performance - Hamjah, Hamjah; Nurzaman, Fahrizal; Sugito, Asep; Munir, Subhi (Pasundan Social Science Development, 2025)
This study aims to explore the role of leadership style, organizational culture, and career development in improving human resource (HR) performance through a qualitative approach. The leadership style applied in an organization can shape communication patterns, motivation, and relationships between leaders and employees, which in turn affect individual performance. Meanwhile, organizational culture formed from shared values, norms, and habits creates a work climate that supports or hinders productivity. Career development also plays an important role in providing opportunities for employees to improve their skills and knowledge, which has an impact on job satisfaction and overall performance. This study uses in-depth interviews and participant observation to explore views from various parties in the organization regarding the influence of these three factors on HR performance. The results show that empowering leadership, positive organizational culture, and support for career development have a close relationship with improving HR performance. These findings provide important insights for organizations to understand how these internal factors can be optimized to achieve better performance.